(untitled) (Kronika Bydgoska, 2010)
The operations of the veterinary medicine service in Bydgoszcz in the scientific and research scope are connected with the functioning of the National Veterinary Research Institute in Puławy Branch in Bydgoszcz (PlWetPIB). The institution, with traditions dating back to the Prussian Department of the Animal Hygiene Institute attached to the Emperor William Royal Agricultural Institute, was developing innovative research in veterinary medicine from the very beginning. Professor Kazimierz Panek stood out particularly; in the inter-war period he conducted innovative research in the scope of physiology and bacteriology. After World War Two, eminent scientists were employees of this institution, e.g. professor E. Domański, professor L. Jaśkowski, and professor E. Wiśniowski, who managed the Animal Hygiene Department in the years 1960-1985. The operations of veterinarians employed by the Municipal Slaughterhouse, and then the Meat Works, were also important. The post-war history of the veterinary medicine service in Bydgoszcz is connected with the operations of the State Veterinary Clinic, whereas the functioning of the Voivodeship Veterinary Inspectorate (WIW) focuses on contemporary issues of the activity of the veterinary medical service in Bydgoszcz.